Mary, Esmeralda, and Frollo: A Hermeneutic Reading of “The Hunchback of Notre Dame – The Musical” - Chrysogonus Siddha Malilang (Institut Seni Indonesia Yogyakarta, 2019)
Mary, Esmeralda, and Frollo: A Hermeneutic Reading of “The Hunchback of Notre Dame – The Musical”. This essay aims to analyze the multimodal storytelling involving songs in The Hunchback of Notre Dame – The Musical. Two songs, “God Helps the Outcasts” and “Hellfire”, are chosen to be analyzed hermeneutically. The primary analysis is done through the scrutiny over the juxtaposition of different musical styles in the said songs. Comparisons to Victor Hugo’s original text and the Disney animated version – in which the musical is based on – is also done to shed more light on the new layers of interpretation.